Classification of Thailand’s industrial firms under global supply chain disruptions: Integrating resilience and sustainability in industrial performance - Watanabe, Woramol C.; Ransikarbum, Kasin; Janmontree, Jettarat (Engineering and Applied Science Research, 2025)
There has been significant disruption of global supply chains as a result of pandemics, geopolitical tensions, and climate-related events. Firms around the world, including those in Thailand, have been compelled to adapt, with increasing emphasis on resilience and sustainability. While many studies have addressed supply chain performance through these lenses, few have focused specifically on the industrial context in Thailand. Moreover, the direction of industrial transformation in response to global challenges remains insufficiently examined. This study addresses these gaps by proposing a comprehensive framework that integrates conventional supply chain performance indicators with resilience and sustainability dimensions. Data were collected from 98 publicly listed industrial firms in Thailand using their 2023 annual reports. Principal component analysis (PCA) was used to identify key performance patterns, and this was followed by K-means clustering to classify firms based on strategic orientation. The analysis revealed four distinct clusters. The largest group, referred to as resilient enterprises (54 firms), demonstrated a balanced performance across efficiency and resilience. Performance-oriented firms (23 firms) exhibited high customer satisfaction, product quality, and flexibility. Agile and lean operators (6 firms) prioritized operational speed and rapid delivery. Flexibility-centric firms (16 firms) focused on adaptability but faced constraints in financial and inventory performance. Overall, the findings indicate that economic factors such as revenue, profitability, and productivity, together with resilience attributes like agility and flexibility, are the primary variables that differentiate firms. This suggests that Thailand’s industrial firms currently place the most emphasis on operational efficiency and adaptability, while broader environmental and social sustainability concerns remain less prominent in strategic differentiation.